KINERJA KOLEKTOR TIPE PLAT DATAR PADA MESIN PENDINGIN ADSORPSI TENAGA SURYA DI KOTA MEDAN - Tulus Burhanuddin Sitorus (Jurnal Teknosains, 2018)
The performance of a flat plate collector on adsorption refrigerator driven by the solar collector was investigated in the present work. Based on a study conducted no researcher studies the performance of solar collectors used in adsorption cooling system. The adsorbent used in the collector was 20 kg ordinary powder activated carbon of coconut shell produced in the Sumatera Utara province of Indonesia, 5 liters of methanol as adsorbate and 6 liters of water as the medium that was cooled. The experiments were carried out under varying weather conditions with total solar radiation about 12619-17807 kJ/m2/cycle in Medan city. The experimental results show that the values of collector efficiency obtained were about 52.11-53.92%. The values of coefficient of performance (COP) obtained were in the range of 0.0318-0.0449. The results of the statistical study suggest that the effect of the weather conditions on collector efficiency thereabout 96%.